Science mapping of the Revista General de Información y Documentación (2005-2022) - Gálvez, Carmen (Revista General de Información y Documentación, 2024)
A study of the Revista General de Información y Documentación (RGID)General Magazine of Information and Documentation (RGID), from 2005 to 2022. The objective is aimed at qualifying the structure of the research field and assessing the trajectory of the thematic areas covered. Applying as methodology the analysis of co-words, the construction of bibliometric networks and the creation of scientific maps. 514 documents are extracted from the Web of Science (WoS) database. The keywords assigned by the authors of the documents are selected and divided into three subperiods: 2005-2010, 2011-2016 and 2017-2022. In the results, 1701 author’s keywords and 37 bibliometric networks are obtained. In the period 2005-2010, the structure of the research field is represented on the scientific map with very few central and specialized topics, considering an initial and underdeveloped organization. In the period 2011-2016, the structure of the research field is distributed on the scientific map with a more varied number of central and specialized topics, but still insufficient, considering an organization in the process of development. In the period 2017-2022, the structure of the research field is shown on the map with all kinds of family of topics (central, specialized, transversal, emerging or disappearing), being valued as a dynamic, complex and heterogeneous organization. Regarding the evolution of the thematic areas, the map shows solid progress between the last two periods. The morphology of the thematic field treated in RGID is outlined in three phases: foundation (2005-2010), process of development (2011-2016) and consolidation (2017-2022).